Effects of a specific training program, in the light of kinematic analysis of the throwing arm, on javelin throwing distance among disabled athletes class F58 - Shalaby Ali, A. R.; Abd El-Ghaffar, W. S. (World Journal of Sport Sciences, 2010)
The current study aims at improving javelin throwing distance among disabled athletes class F58 through identifying kinematic criteria of the throwing arm. The criteria have been identified through existing literature and performance analysis of the World Champion. The study proposes a set of specific exercises according to kinematic criteria of the throwing arm and identifies the effects of these recommended exercises on throwing distance among disabled athletes F58. The researchers employed the quasi-experimental approach on a sample of 8 javelin throwers F58, enrolled in Al-Erada Wa Al-Tahady Sports Club, Kafr El-Shaikh, Egypt. The participants undertook the proposed program and the kinematic criteria and digital level were measured. Results showed that the program led to statistically significant improvement in the digital level (p<= 0.05), in resultant velocity and resultant acceleration of the throwing arm center of gravity and center of gravity of the arm hand in the throwing arm during movement phases (preliminary - main - end). The study also showed statistically significant improvement in the angular velocity and the angular acceleration of elbow joint and in angular acceleration of shoulder joint during the preliminary phase. In addition, the program led to statistically significant improvement in angular velocity of elbow joint and in angular acceleration of shoulder joint during the main phase. Moreover, the program led to statistically significant improvement in the angular velocity of elbow joint and the angular velocity and angular acceleration of shoulder joint during the end phase. The program led to statistically significant improvement in Projection Velocity, Projection angle and the height of Javelin Projection point between pre- and post- test in favor of post-tests, at all levels.